Retinal thinning associates with nigral dopaminergic loss in de novo Parkinson disease. (11th September 2018) - Ahn, Jeeyun; Lee, Jee-Young; Kim, Tae Wan; Yoon, Eun Jin; Oh, Sohee; Kim, Yu Kyeong; Kim, Jong-Min; Woo, Se Joon; Kim, Ki Woong; Jeon, Beomseok
Abstract : Objective: To analyze the relationship between retinal thinning and nigral dopaminergic loss in de novo Parkinson disease (PD). Methods: Forty-nine patients with PD and 54 age-matched controls were analyzed. Ophthalmologic examination and macula optical coherence tomography scans were performed with additional microperimetry, N -(3-[ 18 F]fluoropropyl)-2-carbomethoxy-3-(4-iodophenyl) nortropane PET, and 3T MRI scans were done in patients with PD only. Retinal layer thickness and volume were measured in subfields of the 1-, 2.22-, and 3.45-mm Early Treatment of Diabetic Retinopathy Study circle and compared in patients with PD and controls. Correlation of inner retinal layer thinning with microperimetric response was examined in patients with PD, and the relationships between retinal layer thickness and dopamine transporter densities in the ipsilateral caudate, anterior and posterior putamen, and substantia nigra were analyzed. Results: Retinal layer thinning was observed in the temporal and inferior 2.22-mm sectors (false discovery rate–adjusted p < 0.05) of drug-naive patients with PD, particularly the inner plexiform and ganglion cell layers. The thickness of these layers in the inferior 2.22-mm sector showed a negative correlation with the Hoehn and Yahr stage ( p = 0.032 and 0.014, respectively). There was positive correlation between macular sensitivity and retinal layer thickness in all 3.45-mm sectors, the superior 2.22-mm sector, and 1-mm circle ( p < 0.05 for all). There was an association between retinal thinning and dopaminergic loss in the left substantia nigra (false discovery rate–adjusted p < 0.001). Conclusion: Retinal thinning is present in the early stages of PD, correlates with disease severity, and may be linked to nigral dopaminergic degeneration. Retinal imaging may be useful for detection of pathologic changes occurring in early PD.